Structural, electronic and transport properties of nanoscaled systems - Silva, Francisco Wellery Nunes (2016)
Band structure methods are applied in this work in order to study electronic and transport properties in nano-scaled systems. Density Functional Theory (DFT) has been employed in order to study the electronic properties of a hexagonal island of boron nitrite (hBN) embedded into graphene nanoribbons (GNRs) in both edge chiralities, zigzag and armchair. Furthermore, in our electronic calculation the spin contribution has been taken into account. The results regarding the non-doped systems revealed that a natural spin splitting is associated to the zigzag edged systems, while the armchair one is found to have a spin degenerated ground state. We also investigate the effects due carbon doping in the innermost ring of the h-BN cluster, where the C atom take the place either the Boron or Nitrogen atom. The doping lead to an even more polarized band structure, for energies nearby the Fermi level. The electronic transport properties have been studied applying the Landauer-B¨uttiker formalism, for all proposed systems, and the quantum conductance also exhibit a spin dependence. An application of the systems, as spin dependent molecular sensors is also considered. We have adsorbed different molecules onto electron rich/deficient devices and observed that the electronic conductance may be modulated by those adsorbed systems. Also, in order to verify the thermodynamic stability of the adsorbed systems we have performed Molecular Dynamics calculations under the Nos´e thermostat algorithm. In this thesis, we also have studied the electronic properties of the transition metal dichalcogenides (TMDCs) by means the Slater-Koster tight-binding method for the electronic structure. The electronic transport properties of molybdenum disulfide (MoS2) nanoribbons (MoS2-NR) is considered, and our results show that the edges of the ribbons play an important role in the conductance framework. Our results show that even a small defect due the lack of a MoS2 triplet in the edge is sufficient to lead to a strong suppression of the conductance over the system. Furthermore, interference effects due to defects suggest that MoS2-NR may be applied as nano-diodes.